Flame retardant and corrosion resistant lithium battery shell material and preparation method thereof
By using polypropylene, triallyl phosphate, activated basalt fiber and other materials in the lithium battery shell materials, combined with specific ingredients and mixing processes, the problems of poor flame retardancy and corrosion resistance of existing materials are solved, and the efficient flame retardancy, strength and corrosion resistance of the materials are achieved.
Patent Information
- Application Number
- CN202310617718.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-05-30
AI Technical Summary
The existing lithium battery housing materials have poor performance in flame retardant and corrosion resistance, and the mechanical properties of the materials are reduced after flame retardant.
Polypropylene is used as the base material, combined with triallylphosphate as the flame retardant, activated basalt fibers are used as toughening agent, tris(2,4-di-tert-butylphenyl)phosphite is used as the antioxidant, paraffin is used as the lubricant, aluminum acrylate and carbon black masterbatches are used as auxiliary materials, and flame retardant and corrosion-resistant lithium battery shell materials are prepared through specific ingredients and mixing processes.
The flame retardant performance, impact resistance and corrosion resistance of lithium battery housing materials are significantly improved, ensuring the stability of the material's mechanical properties after flame retardant.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium battery production and manufacturing, and in particular to a flame retardant and corrosion resistant lithium battery shell material and a preparation method thereof. Background Art
[0002] The battery is the heart of an electric vehicle. The specific energy (wh / kg) of the battery determines the driving range of the electric vehicle, and its specific power (w / Kg) affects the maximum speed, acceleration performance and climbing ability of the electric vehicle. Lithium batteries have a history of several decades of development, and the technology is relatively mature, the specific power is also large, the cycle life can reach about 800 to 1000 times, and the cost is relatively low. Therefore, lithium batteries are currently the most widely used batteries for electric vehicles.
[0003] At present, lithium batteries are classified into steel shells, aluminum shells, soft packaging and plastic shells according to their shells. Plastic shell batteries are more suitable for large power tools. The capacity of the battery can be designed arbitrarily according to needs. The application prospects of the battery are very broad. At present, it has great advantages in the application of battery cars and electric motorcycles. However, its research starting point is relatively late. At present, the market mostly uses plastic shells based on polypropylene (PP). Although plastic shell batteries bring great convenience to battery capacity design and promotion and application, plastic shell batteries have problems such as unsatisfactory flame retardancy and corrosion resistance, and the mechanical properties of the material are greatly reduced after flame retardancy.
[0004] Therefore, it is urgent to prepare a flame-retardant and corrosion-resistant lithium battery shell material with good mechanical properties to solve these problems. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a flame retardant and corrosion resistant lithium battery shell material, which includes 30 to 50 parts of polypropylene, 0.02 to 0.2 parts of antioxidants, 10 to 30 parts of toughening agents, 20 to 28 parts of flame retardants, 0.6 to 1 parts of lubricants, 16 to 18 parts of aluminum acrylate, and 0.6 to 1 parts of carbon black masterbatch by weight; the flame retardant includes triallyl phosphate; the toughening agent includes activated basalt fiber.
[0006] Preferably or alternatively, the antioxidant comprises tris(2,4-di-tert-butylphenyl)phosphite.
[0007] Preferably or optionally, the activated basalt fiber has a fiber diameter of 10 to 22 μm and a linear density of 1200 to 4800 tex.
[0008] Preferably or optionally, the lubricant comprises paraffin.
[0009] Preferably or optionally, the resin matrix of the carbon black masterbatch is ethylene-vinyl acetate copolymer, and the carbon black content is 50%.
[0010] Preferably or optionally, a method for preparing a flame retardant and corrosion resistant lithium battery casing material comprises the following preparation steps:
[0011] (1) Ingredients: 30 to 50 parts of polypropylene, 0.02 to 0.2 parts of antioxidant, 10 to 30 parts of toughening agent, 20 to 28 parts of flame retardant, 0.6 to 1 parts of lubricant, 16 to 18 parts of aluminum acrylate, and 0.6 to 1 parts of carbon black masterbatch are mixed by weight;
[0012] (2) Preliminary mixing: 30 to 50 parts by weight of polypropylene, 20 to 28 parts by weight of flame retardant triallyl phosphate, and 3 to 7 parts by weight of initiator are added into a high-speed mixer, the mixing temperature of the high-speed mixer is controlled at 40 to 60° C., and the mixing time is 3 to 5 minutes to obtain a preliminary mixture;
[0013] (3) remixing: adding 16 to 18 parts by weight of aluminum acrylate and 20 to 30 parts by weight of 20% sodium hydroxide solution to the primary mixture, and continuing to mix in a high-speed mixer at 40 to 60° C. for 4 to 8 minutes, and then adding 10 to 30 parts by weight of basalt fiber activated by a toughening agent, 0.6 to 1 part of a lubricant, 0.02 to 0.2 parts of an antioxidant, and 0.6 to 1 part of a carbon black masterbatch, and continuing to mix for 4 to 8 minutes to obtain a remix;
[0014] (4) Preparation of flame-retardant and corrosion-resistant lithium battery shell material: The remixed material is extruded through a twin-screw extruder and cut through a pelletizer to prepare a flame-retardant and corrosion-resistant lithium battery shell material.
[0015] Preferably or optionally, the initiator in step (1) comprises azobisisoheptanonitrile.
[0016] Preferably or optionally, the preparation method of the activated basalt fiber in step (3) is as follows: basalt fiber and concentrated sulfuric acid are mixed at a mass ratio of 1:210-230, ultrasonicated at 30-40kHz for 20-40min, and then 68% concentrated nitric acid is added at a mass fraction of 55-57 times the mass of the basalt fiber.
[0017] The mixture was stirred at 1200-1400 r / min for 9-11 min, heated to 58-62°C, and continued to stir for 1.5-2.5 h. Deionized water (98-102 times the mass of the basalt fiber) was added for dilution. The mixture was allowed to stand for 3.5-4.5 h. The mixture was then vacuum filtered with a microporous filter membrane with a pore size of 220 nm. The mixture was washed with deionized water until the pH value of the filtrate was 7. The mixture was then washed with anhydrous ethanol for 2-4 times. The mixture was dried in an oven at 55-65°C for 40-60 min to obtain activated basalt fiber.
[0018] Preferably or optionally, the screw diameter of the twin-screw extruder in step (4) is 20 to 60 mm, the aspect ratio of the screw is 40:1, and the mixing and melting temperature is 160 to 230°C.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] The flame retardant and corrosion resistant lithium battery shell material prepared by the present invention comprises polypropylene, a flame retardant, a toughening agent, an antioxidant, a lubricant, aluminum acrylate, and a carbon black masterbatch; the flame retardant is triallyl phosphate; the toughening agent is activated basalt fiber; the antioxidant is tris(2,4-di-tert-butylphenyl)phosphite; and the lubricant is paraffin.
[0021] The flame retardant triallyl phosphate is mixed with polypropylene, and the flame retardant triallyl phosphate and the allyl polymerization reaction of polypropylene uniformly disperse the flame retardant in the polypropylene to form a hyperbranched structure of polypropylene, and a large number of cavities are formed in the polypropylene; the activated basalt fiber is quickly dispersed into the polypropylene through the cavity, and the hydroxyl group on the surface of the activated basalt fiber reacts with the carboxyl group on the aluminum acrylate, and the allyl group on the aluminum acrylate and the unsaturated bond on the surface of the cavity are polymerized. The basalt fiber has the properties of light weight, high strength, corrosion resistance, high temperature resistance, etc. The introduction of basalt fiber can enhance the properties of lithium battery shell materials such as light weight, high strength, corrosion resistance, high temperature resistance, and toughness; at the same time, aluminum acrylate is hydrolyzed in an alkaline environment to form aluminum hydroxide gel, which forms an interpenetrating network structure with polypropylene, further enhancing the flame retardant performance, impact resistance and corrosion resistance of the flame retardant and corrosion resistant lithium battery shell material. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the flame retardant and corrosion resistant lithium battery casing materials prepared in the following examples as follows:
[0024] Bending strength: The flame-retardant and corrosion-resistant lithium battery casing materials prepared in the embodiment and the comparative example with the same mass were tested for bending strength according to ASTM D790.
[0025] Tensile strength: The flame-retardant and corrosion-resistant lithium battery casing materials prepared in the embodiment and the comparative example with the same mass were tested for tensile strength according to ASTM D638.
[0026] Flame retardancy: The flame retardant and corrosion-resistant lithium battery casing materials prepared in the embodiment and the comparative example with the same mass were tested for flame retardancy according to UL94.
[0027] Example 1
[0028] A method for preparing a flame retardant and corrosion resistant lithium battery shell material, comprising the following preparation steps:
[0029] (1) Ingredients: 30 parts of polypropylene, 0.02 parts of antioxidant tris(2,4-di-tert-butylphenyl)phosphite, 10 parts of toughening agent activated basalt fiber with a fiber diameter of 10 μm and a linear density of 1200 tex, 20 parts of flame retardant triallyl phosphate, 0.6 parts of lubricant paraffin, 16 parts of aluminum acrylate, 0.6 parts of resin matrix ethylene-vinyl acetate copolymer, and 50% carbon black masterbatch are mixed by weight;
[0030] (2) Preliminary mixing: 30 parts by weight of polypropylene, 20 parts by weight of flame retardant triallyl phosphate, and 3 parts by weight of initiator azobisisoheptanenitrile were added into a high-speed mixer. The mixing temperature of the high-speed mixer was controlled at 40° C. and the mixing time was 3 min to obtain a preliminary mixture.
[0031] (3) Remixing: Add 16 parts by weight of aluminum acrylate and 20 parts by weight of 20% sodium hydroxide solution to the initial mixture, continue mixing in a high-speed mixer at 40° C. for 4 min, then add 10 parts by weight of basalt fiber activated by a toughening agent, 0.6 parts of a lubricant, 0.02 parts of an antioxidant, and 0.6 parts of a carbon black masterbatch, and continue mixing for 4 min to obtain a remix;
[0032] (4) Preparation of flame-retardant and corrosion-resistant lithium battery shell material: The remixed material is extruded through a twin-screw extruder and cut through a pelletizer to prepare a flame-retardant and corrosion-resistant lithium battery shell material.
[0033] The preparation method of the activated basalt fiber in step (3) is as follows: basalt fiber and concentrated sulfuric acid are mixed in a mass ratio of 1:210, ultrasonicated at 30kHz for 20min, then concentrated nitric acid with a mass fraction of 68% which is 55 times the mass of the basalt fiber is added, stirred at 1200r / min for 9min, heated to 58°C, continued to stir for 1.5h, added with deionized water with a mass fraction of 98 times the mass of the basalt fiber for dilution, allowed to stand for 3.5h, then vacuum filtered with a microporous filter membrane with a pore size of 220nm, washed with deionized water until the pH of the filtrate is 7, then washed twice with anhydrous ethanol, and dried in a 55°C oven for 40min to obtain activated basalt fiber.
[0034] The screw diameter of the twin-screw extruder in step (4) is 20 mm, the aspect ratio of the screw is 40:1, and the mixing and melting temperature is 160°C.
[0035] Example 2
[0036] A method for preparing a flame retardant and corrosion resistant lithium battery shell material, comprising the following preparation steps:
[0037] (1) Ingredients: 40 parts of polypropylene, 0.11 parts of antioxidant tris(2,4-di-tert-butylphenyl)phosphite, 20 parts of toughening agent activated basalt fiber with a fiber diameter of 16 μm and a linear density of 3000 tex, 24 parts of flame retardant triallyl phosphate, 0.8 parts of lubricant paraffin, 17 parts of aluminum acrylate, 0.8 parts of resin matrix ethylene-vinyl acetate copolymer, and 50% carbon black masterbatch are mixed by weight;
[0038] (2) Preliminary mixing: 40 parts by weight of polypropylene, 24 parts by weight of flame retardant triallyl phosphate, and 5 parts by weight of initiator azobisisoheptanenitrile were added into a high-speed mixer. The mixing temperature of the high-speed mixer was controlled at 50° C. and the mixing time was 4 min to obtain a preliminary mixture.
[0039] (3) Remixing: Add 17 parts by weight of aluminum acrylate and 25 parts by weight of 20% sodium hydroxide solution to the initial mixture, continue mixing in a high-speed mixer at 50° C. for 5 min, then add 20 parts by weight of basalt fiber activated by a toughening agent, 0.8 parts of a lubricant, 0.11 parts of an antioxidant, and 0.8 parts of a carbon black masterbatch, and continue mixing for 6 min to obtain a remix;
[0040] (4) Preparation of flame-retardant and corrosion-resistant lithium battery shell material: The remixed material is extruded through a twin-screw extruder and cut through a pelletizer to prepare a flame-retardant and corrosion-resistant lithium battery shell material.
[0041] The preparation method of the activated basalt fiber in step (3) is as follows: basalt fiber and concentrated sulfuric acid are mixed in a mass ratio of 1:220, ultrasonicated at 35kHz for 30min, then concentrated nitric acid with a mass fraction of 68% which is 56 times the mass of the basalt fiber is added, stirred at 1300r / min for 10min, heated to 60°C, continued to stir for 2h, added deionized water with a mass fraction of 100 times the mass of the basalt fiber to dilute, let stand for 4h, then vacuum filtered with a microporous filter membrane with a pore size of 220nm, washed with deionized water until the pH of the filtrate is 7, then washed with anhydrous ethanol for 3 times, and placed in a 60°C oven for 50min to obtain activated basalt fiber.
[0042] The screw diameter of the twin-screw extruder in step (4) is 40 mm, the aspect ratio of the screw is 40:1, and the mixing and melting temperature is 190°C.
[0043] Example 3
[0044] A method for preparing a flame retardant and corrosion resistant lithium battery shell material, comprising the following preparation steps:
[0045] (1) Ingredients: 50 parts of polypropylene, 0.2 parts of antioxidant tris(2,4-di-tert-butylphenyl)phosphite, 30 parts of toughening agent activated basalt fiber with a fiber diameter of 22 μm and a linear density of 4800 tex, 28 parts of flame retardant triallyl phosphate, 1 part of lubricant paraffin, 18 parts of aluminum acrylate, and 1 part of a resin matrix of ethylene-vinyl acetate copolymer and a carbon black masterbatch with a carbon black content of 50% are mixed by weight;
[0046] (2) Preliminary mixing: 50 parts by weight of polypropylene, 28 parts by weight of flame retardant triallyl phosphate, and 7 parts by weight of initiator azobisisoheptanenitrile were added into a high-speed mixer. The mixing temperature of the high-speed mixer was controlled at 60° C. and the mixing time was 5 min to obtain a preliminary mixture.
[0047] (3) Remixing: Add 18 parts by weight of aluminum acrylate and 30 parts by weight of 20% sodium hydroxide solution to the initial mixture, continue mixing in a high-speed mixer at 60° C. for 8 min, then add 30 parts by weight of basalt fiber activated by a toughening agent, 1 part of a lubricant, 0.2 parts of an antioxidant, and 1 part of a carbon black masterbatch, and continue mixing for 8 min to obtain a remix;
[0048] (4) Preparation of flame-retardant and corrosion-resistant lithium battery shell material: The remixed material is extruded through a twin-screw extruder and cut through a pelletizer to prepare a flame-retardant and corrosion-resistant lithium battery shell material.
[0049] The preparation method of the activated basalt fiber in step (3) is as follows: basalt fiber and concentrated sulfuric acid are mixed in a mass ratio of 1:230, ultrasonicated at 40kHz for 40min, then concentrated nitric acid with a mass fraction of 68% which is 57 times the mass of the basalt fiber is added, stirred at 1400r / min for 11min, heated to 62°C, continued to stir for 2.5h, added deionized water with a mass of 102 times the mass of the basalt fiber to dilute, let stand for 4.5h, then vacuum filtered with a microporous filter membrane with a pore size of 220nm, washed with deionized water until the pH of the filtrate is 7, then washed with anhydrous ethanol for 4 times, and placed in a 65°C oven for 60min to obtain activated basalt fiber.
[0050] The screw diameter of the twin-screw extruder in step (4) is 60 mm, the aspect ratio of the screw is 40:1, and the mixing and melting temperature is 230°C.
[0051] Comparative Example 1
[0052] A method for preparing a flame retardant and corrosion resistant lithium battery shell material, comprising the following preparation steps:
[0053] (1) Ingredients: 40 parts of polypropylene, 0.11 parts of antioxidant tris(2,4-di-tert-butylphenyl)phosphite, 20 parts of toughening agent activated basalt fiber with a fiber diameter of 16 μm and a linear density of 3000 tex, 0.8 parts of lubricant paraffin, 17 parts of aluminum acrylate, 0.8 parts of resin matrix ethylene-vinyl acetate copolymer, and 50% carbon black masterbatch are mixed by weight;
[0054] (2) Preliminary mixing: 40 parts by weight of polypropylene and 5 parts by weight of initiator azobisisobutyronitrile were added into a high-speed mixer. The mixing temperature of the high-speed mixer was controlled at 50° C. and the mixing time was 4 min to obtain a preliminary mixture.
[0055] (3) Remixing: Add 17 parts by weight of aluminum acrylate and 25 parts by weight of 20% sodium hydroxide solution to the initial mixture, continue mixing in a high-speed mixer at 50° C. for 5 min, then add 20 parts by weight of basalt fiber activated by a toughening agent, 0.8 parts of a lubricant, 0.11 parts of an antioxidant, and 0.8 parts of a carbon black masterbatch, and continue mixing for 6 min to obtain a remix;
[0056] (4) Preparation of flame-retardant and corrosion-resistant lithium battery shell material: The remixed material is extruded through a twin-screw extruder and cut through a pelletizer to prepare a flame-retardant and corrosion-resistant lithium battery shell material.
[0057] The preparation method of the activated basalt fiber in step (3) is as follows: basalt fiber and concentrated sulfuric acid are mixed in a mass ratio of 1:220, ultrasonicated at 35kHz for 30min, then concentrated nitric acid with a mass fraction of 68% which is 56 times the mass of the basalt fiber is added, stirred at 1300r / min for 10min, heated to 60°C, continued to stir for 2h, added deionized water with a mass fraction of 100 times the mass of the basalt fiber to dilute, let stand for 4h, then vacuum filtered with a microporous filter membrane with a pore size of 220nm, washed with deionized water until the pH of the filtrate is 7, then washed with anhydrous ethanol for 3 times, and placed in a 60°C oven for 50min to obtain activated basalt fiber.
[0058] The screw diameter of the twin-screw extruder in step (4) is 40 mm, the aspect ratio of the screw is 40:1, and the mixing and melting temperature is 190°C.
[0059] Comparative Example 2
[0060] A method for preparing a flame retardant and corrosion resistant lithium battery shell material, comprising the following preparation steps:
[0061] (1) Ingredients: 40 parts of polypropylene, 0.11 parts of antioxidant tris(2,4-di-tert-butylphenyl)phosphite, 24 parts of flame retardant triallyl phosphate, 0.8 parts of lubricant paraffin, 17 parts of aluminum acrylate, 0.8 parts of resin matrix ethylene-vinyl acetate copolymer, and 50% carbon black masterbatch are mixed by weight;
[0062] (2) Preliminary mixing: 40 parts by weight of polypropylene, 24 parts by weight of flame retardant triallyl phosphate, and 5 parts by weight of initiator azobisisoheptanenitrile were added into a high-speed mixer. The mixing temperature of the high-speed mixer was controlled at 50° C. and the mixing time was 4 min to obtain a preliminary mixture.
[0063] (3) Remixing: Add 17 parts by mass of aluminum acrylate and 25 parts by mass of 20% sodium hydroxide solution to the initial mixture, continue mixing in a high-speed mixer at 50° C. for 5 min, then add 0.8 parts of lubricant, 0.11 parts of antioxidant, and 0.8 parts of carbon black masterbatch, and continue mixing for 6 min to obtain a remix;
[0064] (4) Preparation of flame-retardant and corrosion-resistant lithium battery shell material: The remixed material is extruded through a twin-screw extruder and cut through a pelletizer to prepare a flame-retardant and corrosion-resistant lithium battery shell material.
[0065] The screw diameter of the twin-screw extruder in step (4) is 40 mm, the aspect ratio of the screw is 40:1, and the mixing and melting temperature is 190°C.
[0066] Comparative Example 3
[0067] A method for preparing a flame retardant and corrosion resistant lithium battery shell material, comprising the following preparation steps:
[0068] (1) Ingredients: 40 parts of polypropylene, 0.11 parts of antioxidant tris(2,4-di-tert-butylphenyl)phosphite, 20 parts of toughening agent activated basalt fiber with a fiber diameter of 16 μm and a linear density of 3000 tex, 24 parts of flame retardant triallyl phosphate, 0.8 parts of lubricant paraffin, 0.8 parts of resin matrix ethylene-vinyl acetate copolymer, and 50% carbon black masterbatch are mixed by weight;
[0069] (2) Preliminary mixing: 40 parts by weight of polypropylene, 24 parts by weight of flame retardant triallyl phosphate, and 5 parts by weight of initiator azobisisoheptanenitrile were added into a high-speed mixer. The mixing temperature of the high-speed mixer was controlled at 50° C. and the mixing time was 4 min to obtain a preliminary mixture.
[0070] (3) Remixing: Add 25 parts by mass of 20% sodium hydroxide solution to the initial mixture, continue mixing in a high-speed mixer at 50° C. for 5 min, then add 20 parts by mass of basalt fiber activated by a toughening agent, 0.8 parts of a lubricant, 0.11 parts of an antioxidant, and 0.8 parts of a carbon black masterbatch, and continue mixing for 6 min to obtain a remix;
[0071] (4) Preparation of flame-retardant and corrosion-resistant lithium battery shell material: The remixed material is extruded through a twin-screw extruder and cut through a pelletizer to prepare a flame-retardant and corrosion-resistant lithium battery shell material.
[0072] The preparation method of the activated basalt fiber in step (3) is as follows: basalt fiber and concentrated sulfuric acid are mixed in a mass ratio of 1:220, ultrasonicated at 35kHz for 30min, then concentrated nitric acid with a mass fraction of 68% which is 56 times the mass of the basalt fiber is added, stirred at 1300r / min for 10min, heated to 60°C, continued to stir for 2h, added deionized water with a mass fraction of 100 times the mass of the basalt fiber to dilute, let stand for 4h, then vacuum filtered with a microporous filter membrane with a pore size of 220nm, washed with deionized water until the pH of the filtrate is 7, then washed with anhydrous ethanol for 3 times, and placed in a 60°C oven for 50min to obtain activated basalt fiber.
[0073] The screw diameter of the twin-screw extruder in step (4) is 40 mm, the aspect ratio of the screw is 40:1, and the mixing and melting temperature is 190°C.
[0074] Effect example
[0075] Table 1 below shows the analysis results of the bending strength, tensile strength and flame retardant properties of the flame retardant and corrosion resistant lithium battery casing materials prepared using Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.
[0076] Table 1
[0077] Bending strength(MPa) Tensile strength(MPa) Vertical burning level Example 1 152 108 V-0 Example 2 162 116 V-0 Example 3 159 114 V-0 Comparative Example 1 101 76 V-1 Comparative Example 2 98 103 V-0 Comparative Example 3 113 85 V-2
[0078] It can be found from Table 1 that the bending strength, tensile strength and flame retardant properties of the flame retardant and corrosion resistant lithium battery shell materials prepared in Examples 1, 2 and 3 are good; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1, it can be found that the use of the flame retardant triallyl phosphate to prepare the flame retardant and corrosion resistant lithium battery shell material has good bending strength, tensile strength and flame retardant properties; from the experimental data of Examples 1, 2, 3 and Comparative Example 2, it can be found that the use of basalt fiber activated by a toughening agent to prepare the flame retardant and corrosion resistant lithium battery shell material has good bending strength and tensile strength; from the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that the use of acrylic aluminum to prepare the flame retardant and corrosion resistant lithium battery shell material has good bending strength, tensile strength and flame retardant properties.
[0079] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A flame retardant and corrosion resistant lithium battery shell material, characterized in that: The composition comprises 30-50 parts of polypropylene, 0.02-0.2 parts of antioxidant, 10-30 parts of toughening agent, 20-28 parts of flame retardant, 0.6-1 parts of lubricant, 16-18 parts of aluminum acrylate, and 0.6-1 parts of carbon black masterbatch by weight; the flame retardant comprises triallyl phosphate; the toughening agent comprises activated basalt fiber; A method for preparing a flame retardant and corrosion resistant lithium battery shell material, comprising the following preparation steps: (1) Ingredients: 30-50 parts of polypropylene, 0.02-0.2 parts of antioxidant, 10-30 parts of toughening agent, 20-28 parts of flame retardant, 0.6-1 parts of lubricant, 16-18 parts of aluminum acrylate, and 0.6-1 parts of carbon black masterbatch are mixed by weight; (2) Primary mixing: 30-50 parts by weight of polypropylene, 20-28 parts by weight of flame retardant triallyl phosphate, and 3-7 parts by weight of initiator are added into a high-speed mixer. The mixing temperature of the high-speed mixer is controlled at 40-60°C and the mixing time is 3-5 minutes to obtain a primary mixture. (3) Remixing: Add 16-18 parts by weight of aluminum acrylate and 20-30 parts by weight of 20% sodium hydroxide solution to the initial mixture, continue mixing in a high-speed mixer at 40-60° C. for 4-8 minutes, then add 10-30 parts by weight of basalt fiber activated by a toughening agent, 0.6-1 parts of a lubricant, 0.02-0.2 parts of an antioxidant, and 0.6-1 parts of a carbon black masterbatch, continue mixing for 4-8 minutes to obtain a remix; (4) Preparation of flame-retardant and corrosion-resistant lithium battery shell material: extruding the remixed material through a twin-screw extruder and cutting it through a pelletizer to prepare a flame-retardant and corrosion-resistant lithium battery shell material; The preparation method of the activated basalt fiber in step (3) is as follows: basalt fiber and concentrated sulfuric acid are mixed in a mass ratio of 1:210-230, ultrasonicated at 30-40 kHz for 20-40 min, then concentrated nitric acid with a mass fraction of 68% which is 55-57 times the mass of the basalt fiber is added, stirred at 1200-1400 r / min for 9-11 min, heated to 58-62° C., continued to stir for 1.5-2.5 h, added deionized water with a mass fraction of 98-102 times the mass of the basalt fiber to dilute, allowed to stand for 3.5-4.5 h, then vacuum filtered with a microporous filter membrane with a pore size of 220 nm, washed with deionized water until the pH value of the filtrate is 7, then washed with anhydrous ethanol for 2-4 times, and dried in an oven at 55-65° C. for 40-60 min to obtain activated basalt fiber.
2. The flame retardant and corrosion resistant lithium battery casing material according to claim 1, characterized in that: The antioxidant includes tris(2, 4-di-tert-butylphenyl)phosphite.
3. The flame retardant and corrosion resistant lithium battery casing material according to claim 1, characterized in that: The activated basalt fiber has a fiber diameter of 10-22 μm and a linear density of 1200-4800 tex.
4. The flame retardant and corrosion resistant lithium battery casing material according to claim 1, characterized in that: The lubricant includes paraffin.
5. The flame retardant and corrosion resistant lithium battery casing material according to claim 1, characterized in that: The resin matrix of the carbon black masterbatch is ethylene-vinyl acetate copolymer, and the carbon black content is 50%.
6. The flame retardant and corrosion resistant lithium battery casing material according to claim 1, characterized in that: The initiator in step (2) includes azobisisoheptanonitrile.
7. The flame retardant and corrosion resistant lithium battery casing material according to claim 1, characterized in that: The screw diameter of the twin-screw extruder in step (4) is 20-60 mm, the aspect ratio of the screw is 40:1, and the mixing and melting temperature is 160-230°C.
Citation Information
Patent Citations
Lithium battery case flame-retardant material based on long-glass-fiber-reinforced polypropylene and preparation method thereof
CN103113706A
Ethylene-alpha-olefin copolymer-triallyl phosphate composition
CN110312757A